Prevalence and Potential Risk Factors of Peyronie’s Disease: A Cross-Sectional Study of 68 Cases - Hosseini, Jalil; Rahimi Gorji, Mohammad; Safdarian, Ali; Karimi, Sara; Safari, Saeed (Archives of Men's Health, 2025)
Introduction: Peyronie’s disease (PD) is characterized by the formation of fibrous, scar-like tissue in one or more areas of the tunica albuginea. Several potential risk factors for PD have been investigated. We aimed to evaluate the frequency of potential risk factors in PD patients. Methods: In this retrospective cross-sectional study, we included men diagnosed with PD who presented to a referral outpatient urology clinic between March 2019 and August 2024, in Tehran, Iran. Due to the relatively low prevalence of PD and the study's focus on specific risk factors within this population, purposive sampling was employed. The frequency of potential risk factors and the correlation between different risk factors were assessed. Results: A total of 68 patients with PD were studied. The mean age of the disease onset was 53.7 ± 8.0 (range: 28–72) years. The most prevalent risk factors were DM in 20 (29.4%) patients and smoking in 18 (26.5%) patients. There was no significant difference regarding the frequency of risk factors between the two age groups of <55 and ≥55 years (P > 0.05 for all risk factors). Among patients with diabetes mellitus (DM), the median duration of DM since diagnosis was 8.5 (IQR: 2–30) years, while the median duration of hypertension among hypertensive patients was 10 (IQR: 4–20) years. For smokers, the median cumulative smoking exposure was 20 (IQR: 10 – 30) pack-years. Patients who developed PD before the age of 55 had a significantly longer duration of DM compared to those who presented with the disease at ≥55 years (15 vs. 5 years; p = 0.039). Correlation analysis revealed a strong positive correlation between the use of vasoactive erectile drugs and erectile dysfunction (r = 0.64). A negative correlation was observed between a history of penile trauma and age of PD onset (r = -0.40). Conclusion: Based on the findings of the present study, the most frequent potential risk factors were DM and smoking in this series of PD cases. The longer duration of DM may be associated with an earlier onset of PD and its presentation in ages < 55 years.